Catching the wind : Edward Kennedy and the liberal hour - Gabler, Neal (Crown, 2020)
"The epic, definitive biography of Ted Kennedy--an immersive journey through the life of a complicated man and a sweeping history of the fall of liberalism and the collapse of political morality. Edward M. Kennedy was never expected to succeed. The youngest of nine, he lacked his brothers' natural gifts and easy grace. Yet after winning election to the Senate at the tender age of thirty, he became the most consequential legislator of his lifetime, perhaps even American history. Surviving the traumas of his brothers' assassinations, Ted Kennedy ultimately exerted the greatest effort keeping alive the mission of an active and caring government. He swept into the Senate at the high-water mark of the mid-century New Deal consensus and fulfilled the promise of that momentum throughout his glory years in the Senate as the booming voice of American liberalism. That voice found its greatest impact in the laws he passed that wove government firmly into American life, extending aid and opportunity to those in most desperate need. Two thousand pieces of legislation, ranging from health care to education to civil rights, bore Ted's fingerprints. He worked tirelessly to better people's lives, even after the Reagan-era push for limited government rewrote the contract between nation and citizens. He did this because he felt he owed it to those who suffered, and those with whom he empathized out of his own pain and ever-present sense of inadequacy. But Ted Kennedy was not immune to the darkness that plagued his family. He lived long enough to fail, to sin, to fall in and out of favor. The infamous incident at Chappaquiddick marked an unfortunate turning point in the youngest Kennedy's life, and it would not be his last brush with controversy. As his personal failures compounded in the public eye, he struggled to maintain the traction that had carried his agenda so far. The product of a decade of work and hundreds of interviews, Catching the Wind will be an essential work of history and biography. The first of two volumes in a sweeping narrative, it traces the extraordinary life of an American statesman from his early years through the turning point of the 1970s. It is a landmark study of legislative genius and a powerful exploration of the man who spent his career upholding his mandate in service of a better America"--